Über das Leben Raffaels von Urbino - Die Göttinger Vorlesung aus dem Jahr 1841 - Oesterley, Carl Wilhelm Friedrich (Universitätsverlag Göttingen, 2019)
Presenting the previously unpublished lecture notes of 'Über das Leben Raffaels von Urbino' by Carl Wilhelm Friedrich Oesterley, a lecture series given in spring 1841 at the University of Göttingen, this edition sheds light on a major step contribution to the research on Raphael and academic teaching in the 19th century. The manuscript draws on the seminal study of Johann David Passavant on Raphael and his father Giovanni Santi, published two years earlier in 1839. The volume presents a collection of studies on Oestlerley's role within the reception of Raphael in the Romanticism and on his career as painter, arthistorian and as curator of the university art collection in Göttingen. Based on numerous original sources, the edition offers an insight into the academic teaching in the mid-19th century.